(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
This article discusses the plant life cycle and the main genetic regulatory mechanisms controlling growth, development, and reproduction. It describes the transitions between developmental stages, the role of hormones, gene expression networks, epigenetic regulation, and environmental signaling pathways.